As estratégias missionárias da Igreja Evangélica Luterana de Angola (IELA) no contexto atual de Angola - Velho, Mário Passala (2012)
This paper attempts to analyze the missionary strategies of Lutheran character that have been developed in the context of the Evangelical Lutheran Church of Angola (ELCA) since its inception to the present day. The social and political conditions, economic difficulties and armed conflicts have been characterized as an atmosphere of many limitations to the missionary work of the ELCA, because the conditions are always presenting themselves in the midst of very limiting geopolitical difficulties of missionary work and pastoral care. The ELCA search paths that toward autonomy in the broad sense. To this end, the research wants to help in understanding the context in which it is allowing certain perception of the limits and possibilities of a lutheran missionary action in Angola.